1355. Resistance in Gram-Negative Bacteria in the Pediatric Patient Population by Age and Sex. (31st December 2020) - Malamet, Benjamin J; Sims, Matthew
Abstract: Background: Previous research within the Beaumont Infectious Diseases Research Program found an overall increase in antibiotic resistance in adult males versus females. Furthermore, there is a peak in resistance in 18-29-year-old males, not seen in females. The origin of this early peak of antibiotic resistance in adults is unclear. This study examines these trends in the pediatric patient population. Methods: Resistance data for all Gram-negative bacterial clinical isolates from Beaumont Health System's clinical microbiology lab between October 1st, 2010, and December 31st, 2014 was analyzed. The pediatric isolates were categorized into sextiles (0-2, 3-5, 6-8, 9-11, 12-14, 15-17) and the sensitivities for each antibiotic were compared based on gender and age and separated by urine isolates vs. non-urine isolates to account for potential bias based on an abundance of urine samples in females. Results: There were 7878 pediatric Gram-negative bacterial isolates in the database, and 96 duplicate samples were removed, leaving 7782 isolates to be analyzed. There were more female isolates (n=6888) than male isolates (n=890) due to the preponderance of urine cultures in females. At most age ranges, antibiotic resistance was significantly higher in males than females. In males, antibiotic resistance was highest between 12-14 and 15-17 years old. When analyzing the cultures based on sample type, the peak in resistance in males is seen in urine isolates, but the patterns of resistance are chaotic in non-urine isolates. This is likely attributable to a low number of isolates. Conclusion: Sex is an important factor in determining antibiotic resistance in the pediatric patient population, as males exhibit higher resistance. The peak in antibiotic resistance initially noted in 18-29-year-old males in previous research originates in the pediatric age group and appears to develop between 12-17 years old. Further research is needed to determine the cause of the observed gender bias, to ascertain if it is modifiable in order to reduce antibiotic resistance. Disclosures: All Authors : No reported disclosures